Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/ju.0000000000001364
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Surveillance, Primary Chemotherapy, Radiotherapy and Retroperitoneal Lymph Node Dissection for the Management of Early Stage Testicular Germ Cell Tumors: A Systematic Review

Abstract: confirm institutions and author initials in parentheses are correct as presented.Purpose: Cancer specific survival for men with early stage (I to IIB) testicular germ cell tumors is greater than 90% with any management strategy. The data regarding the comparative effectiveness of surveillance, primary chemotherapy, radiotherapy and retroperitoneal lymph node dissection were synthesized with a focus on oncologic outcomes, patient reported outcomes, and short and long-term toxicities. Materials and Methods: PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
0
15
0
3
Order By: Relevance
“…Although men with early‐stage TGCTs usually experience excellent cancer‐specific survival, ranging between 94% and 100%, the prognosis and the risk of relapse in our patient remain uncertain due to the rarity of the histopathological finding and the short follow‐up (Pierorazio et al., 2021).…”
Section: Discussionmentioning
confidence: 90%
“…Although men with early‐stage TGCTs usually experience excellent cancer‐specific survival, ranging between 94% and 100%, the prognosis and the risk of relapse in our patient remain uncertain due to the rarity of the histopathological finding and the short follow‐up (Pierorazio et al., 2021).…”
Section: Discussionmentioning
confidence: 90%
“…All large vessels need to be skeletal. RPLND is prone to erectile dysfunction, lymphatic leakage (lymphedema, chylous ascites), surgical injury (most commonly vascular injury and ureteral injury), surgical infection (lung, incision), intestinal obstruction and other complications ( 24 , 25 ). Besides, infertility was the major long-term toxicity associated with RPLND ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This practice was driven by the data which showed excellent outcomes can be achieved with less intensive therapy while simultaneously reducing treatment-related toxicity. 9 Active surveillance is also shown to be the most cost-effective modality of treatment. 10 Our previous study using the same database has shown that active surveillance is now the most common treatment strategy for patients with stage I testicular cancer in Ontario.…”
Section: Discussionmentioning
confidence: 99%